OSMONAALY KYDYK-UULU SYDYKOV – AS A KYRGYZ ETHNOGRAPHER (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The creative heritage of Osmonaaly Kydyk-uulu Sydykov, one of the intellectuals who founded the written history traditions of the Kyrgyz people, reflects, in addition to rich genealogical information, also the changes in the Kyrgyz society in the 19th and early 20th centuries in an original way. The article focuses on the information reflecting various aspects of the ethnography of the Kyrgyz people in two books by Osmonaaly Sydykov, published in the city of Ufa in 1913 and 1914
Keywords: ethnography, traditions, intangible cultural heritage, Kyrgyz, genealogy, written source studies, historiography, Ural, Volga, Turkestan